The Problem of Cultural Exception in the Courts - Hercus Pereira dos Santos (Jurnal Ilmu Hukum, 2026)
As we know that we men always live within a culture and this culture at the same time is the product of human beings, but then men must subjugate to this culture that they produce, that is, the culture that men produce will then shape the way men think, perceive and act in life. Man and culture have an inseparable relationship and that the culture that men create later, this culture is what will regulate the lives of men. But then there are some cultural practices that can contradict state norms – positive law, and that can create major conflicts with the International System for the Protection of Human Rights. This reality as a challenge that Timor-Leste seeks to solve and the solution that Timor-Leste takes is to value cultures that do not contradict state law and Human Rights. It prohibits and penalizes cultural practices that contradict state law and Human Rights. Timor-Leste as a member state of the United Nations and which is also part as a member of UNESCO (United Nations Educational, Scientific and Cultural Organization) as of November 3, 2003 has its commitment to value the local culture of its people. But Timor-Leste also shows its strong commitment also to the protection of Human Rights since its independence where Timor-Leste has already ratified many international instruments for the protection of Human Rights. Therefore, this shows that, Timor-Leste, on the one hand, must value and guarantee the citizen's right to culture, but on the other hand, Timor-Leste must protect the human rights of every citizen. In the legal system of many countries and also in the Timorese legal system, we can say that there is room to give importance to culture in the Court, but it must give greater primacy to state law (positive law) and the International Human Rights System in any decision that the Court takes. Cultural issues can be valued and considered when they help to better interpret respect in the application of state-positive law and international human rights systems.